Addie Model-Based Training Management As An Effort To Improve Employee Competence (Case Study At Ramayana Department Store Salatiga) - Kristin Tiwow; Agus Sugiarto (Journal Research of Social Science, Economics, and Management, 2024)
The purpose of this study is to investigate how Ramayana Department Store Salatiga has implemented training management using the five stages of the ADDIE model: analysis, design, development, implementation, and evaluation. An exploratory qualitative method was employed in this investigation. Interviews with many Ramayana Department Store resource people were done. Five individuals served as the study's resources: the head office, the store manager, the HR supervisor, the consignment team, and the employees. Based on the study's findings, Ramayana has implemented training management using ADDIE in line with many stages, including analysis, planning, development, implementation, and assessment. In order to ensure that this training supports Ramayana's vision and goal, it is necessary to design a few stages, namely the implementation and assessment stages. Ramayana has performed training to the fullest extent possible at each level.